A dipole-assisted solid-phase extraction microchip combined with inductively coupled plasma-mass spectrometry for online determination of trace heavy metals in natural water. Issue 2 (26th November 2014) - Shih, Tsung-Ting; Hsu, I-Hsiang; Chen, Shun-Niang; Chen, Ping-Hung; Deng, Ming-Jay; Chen, Yu; Lin, Yang-Wei; Sun, Yuh-Chang
Abstract : A microchip was modified with C–Cl moieties for the development of an on-chip dipole-assisted solid-phase extraction technique. Abstract : We employed a polymeric material, poly(methyl methacrylate) (PMMA), for fabricating a microdevice and then implanted the chlorine (Cl)-containing solid-phase extraction (SPE) functionality into the PMMA chip to develop an innovative on-chip dipole-assisted SPE technique. Instead of the ion–ion interactions utilized in on-chip SPE techniques, the dipole–ion interactions between the highly electronegative C–Cl moieties in the channel interior and the positively charged metal ions were employed to facilitate the on-chip SPE procedures. Furthermore, to avoid labor-intensive manual manipulation, a programmable valve manifold was designed as an interface combining the dipole-assisted SPE microchip and inductively coupled plasma-mass spectrometry (ICP-MS) to achieve the fully automated operation. Under the optimized operation conditions for the established system, the detection limits for each analyte ion were obtained based on three times the standard deviation of seven measurements of the blank eluent solution. The limits ranged from 3.48 to 20.68 ng L −1, suggesting that this technique appears uniquely suited for determining the levels of heavy metal ions in natural water. Indeed, a series of validation procedures demonstrated that the developed method could be satisfactorily applied to the determination of trace heavy metals in natural water. Remarkably, the developed device was durable enough to be reused more than 160 times without any loss in its analytical performance. To the best of our knowledge, this is the first study reporting on the combination of a dipole-assisted SPE microchip and elemental analysis instrument for the online determination of trace heavy metal ions.